Sustainability Practices in Nigeria Higher Education Institutions: The Case Study of a Public Tertiary Institution in North Western Region of Nigeria - Abenu, Abigail; Yusufu, Funmilayo Alfa; Ugochukwu, Precious Juliet (Journal of Sustainability and Environmental Management, 2024)
In many developed nations, higher education institutions (HEIs) are increasingly promoting environmental sustainability through their teaching, research, operations, and practices. However, many HEIs in Africa have yet to give sustainability practices significant attention. This study appraises the current status of sustainability in one public higher education institution in Nigeria and the challenges that inhibit the integration of sustainability into its operations and practices. The survey included 141 randomly selected undergraduates and 5 purposively selected staff members. The results reveal that the school has made progress in teaching courses that promote environmental sustainability. However, only limited achievements have been made in integrating sustainability into its operations and practices. The major challenges of environmental sustainability in the school are the absence of a formal sustainability policy, lack of funds, and the absence of designated offices and positions for sustainability. Significant progress in sustainability education and practices can be achieved through the formulation of a sustainability policy, greater collaboration with other HEIs, and the establishment of sustainability offices and positions.